Firm leadership and the gender pay gap: do active owners discriminate more than hired managers? - Boris Hirsch; Steffen Mueller (Journal for Labour Market Research, 2014)
Using a large linked employer-employee data set for Germany, we investigate differences in the unexplained gender pay gap between owner-run and manager-run firms. We hypothesise that owner-managers and hired managers differ in their discretion to engage in profit-reducing taste discrimination against women, which would translate into different pay gaps depending on leadership regime. We find that unexplained gaps are significantly higher in owner-run firms, both statistically and economically. Yet, scrutinising these results by restricting our analysis to firms that only differ in leadership regime, this substantial difference disappears. Therefore, our findings do not support that active owners are more discriminatory per se.
Keywords: J31; J16; J71; 330; Unternehmensführung - Auswirkungen; Lohnunterschied; geschlechtsspezifische Faktoren; erwerbstätige Frauen; erwerbstätige Männer; Lohndiskriminierung; Geschäftsführer; abhängig Beschäftigte; Unternehmer; Führungskräfte; IAB-Linked-Employer-Employee-Datensatz